Singapore in global history - Heng, Derek Thiam Soon; Aljunied, Syed Muhd Khairudin (ICAS publication series, 2011)
Globalising the history of Singapore Syed Muhd Khairudin Aljunied & Derek Heng -- Situating Temaski within the larger regional context : maritime Asia and Malay state formation in the pre-modern era Derek Heng -- The Singapore River : port in a global context Stephen Dobbs -- 'Walls of illusion' : information generation in colonial Singapore and the reporting of the Mahdi-Rebellion in Sudan, 1887-1890 Torsten Tschacher -- The littoral and the literary : making moral communities in the Straits Settlements and the Gold Coast in the late nineteenth and early twentieth century Philip Holden -- Social discourse and economic functions : the Singapore Chinese in Japan's southward expansion between 1914 and 1941 Huei-Ying Kuo -- The dynamics of trans-regional business and national politics : the impact of events in China on Fujian-Singapore tea trading networks, 1920-1960 Jason Lim -- Rambutans in the picture : Han Wai Toon and the articulation of space by the overseas Chinese in Singapore Lai Chee Kien -- The global effects of an ethnic riot : Singapore, 1950-1954 Syed Muhd Khairudin Aljunied -- The British military withdrawal from Singapore and the anatomy of a catalyst Loh Kah Seng -- Bringing the international and transnational back in : Singapore, decolonisation, and the Cold War S.R. Joey Long -- The global and the regional in Lee Kuan Yew's strategic thought : the early Cold War years Ang Cheng Guan -- Brief history of the hub : navigating between 'global' and 'Asian' in Singapore's knowledge economy discourse Leong Yew
Includes bibliographical references (p. [297]-317)
Keywords: Singapore -- History; Singapore -- Politics and government -- Singapore -- History; Singapore -- Politics and government; Aufsatzsammlung; Geschichte; Singapur